2021
DOI: 10.1002/biof.1793
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol attenuates high‐fructose diet‐induced inflammation and insulin resistance via inhibition of 11β‐hydroxysteroid dehydrogenase type 1 activity in rat adipose tissues

Abstract: High fructose consumption has been linked to low-grade inflammation and insulin resistance that results in increased intracellular 11ß-hydroxysteroid dehydrogenase type 1 (11β-HSD1) activity. Celastrol, a pentacyclic triterpene, has been demonstrated to exhibit multifaceted targets to attenuate various metabolic diseases associated with inflammation. However, the underlying mechanisms by which celastrol exerts its attributive properties on high fructose diet (HFrD)-induced metabolic syndrome remain elusive. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
(221 reference statements)
0
0
0
Order By: Relevance
“…Clinical trials have demonstrated the safety and efficacy of 11β-HSD1 inhibition in ameliorating liver steatosis and IR 29 , 62 , 63 . Furthermore, 11β-HSD1 inhibition mitigates hyperlipidemia, liver inflammation, and fibrosis in MASLD models 30 , 64 - 67 . And Hsd11b1 (11β-HSD1) gene deficiency shields mice against glucose intolerance, dyslipidemia, and obesity 68 .…”
Section: Discussionmentioning
confidence: 94%
“…Clinical trials have demonstrated the safety and efficacy of 11β-HSD1 inhibition in ameliorating liver steatosis and IR 29 , 62 , 63 . Furthermore, 11β-HSD1 inhibition mitigates hyperlipidemia, liver inflammation, and fibrosis in MASLD models 30 , 64 - 67 . And Hsd11b1 (11β-HSD1) gene deficiency shields mice against glucose intolerance, dyslipidemia, and obesity 68 .…”
Section: Discussionmentioning
confidence: 94%